Peran Civil Law Dalam Sistem Hukum Indonesia - Tri Bowo Hersandy Febrianto (International Forum of Researchers and Lecturers, 2024)
The legal problems currently developing are of various forms and types, so legal codification must be adapted to these developments. Since the decade of Indonesia's independence, civil law has been used as the axis of the national legal system which aims to create legal certainty. Certainty and justice are not something new in the Indonesian legal system, this is the role of judges to create laws based on applicable laws and regulations. This research aims to explain the role of civil law as a national legal system applied by Indonesia to create law. The normative juridical approach method is an approach based on the main legal material by examining theories, concepts, legal principles and statutory regulations. The results of the research show that civil law still has an important role in the legal system in Indonesia, but legal codification needs to be adapted to increasingly advanced developments so that legal events that occur are still contained in statutory regulations.